Capitalism without Conscience - Santi, Michel (Peter Lang International Academic Publishing Group, 2014)
Does austerity aim to reduce the deficits or is it but a pretext to move the state backwards, demolishing in the process what remains of social programs? It would now be a good time recall Keynes who concluded his «General Theory» with a call for the «socialization» of investment - a business too serious to be left in the hands of financial markets.